2020
DOI: 10.32682/sastranesia.v8i1.1353
|View full text |Cite
|
Sign up to set email alerts
|

Spell of Ende Language in Uzuzoza Village of Ende Regency Mantra Bahasa Ende Di Desa Uzuzoza Kabupaten Ende

Abstract: The research is about the spell of Ende Language in Uzuzoza village of Ende Regency based on two main problems, that was finding and describing spell’sform and it’s function. For gathering the data, the research used was an interview and listen tomethod with see, and capable techniques. Formal technique analysis is usedas data analysis of this research. The old theory of literature is used of this research with the concideration that the spell developed in the traditional era in animism and dynamism by using o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Studies on traditional healing practices within the Lio community have encompassed the documentation of Nijo healing ) and the compilation of a lexicon related to Lio healing practices (Genua 2018). Other folk medicine studies within the Lio community have focused on documenting Sua Soza, a healing mantra in the Ende language (Bala and Hua 2020), and the documentation of the Tu Gelu healing ritual, which involves the treatment of mystical ailments through the mediation of a traditional healer, involving the exchange of items representing livestock (Wula and Mboka 2021). Additionally, ethnobotanical studies recording the plant species utilized by the Lio people for traditional healing have shown that there are 47 plant species in the village of Waturaka and 52 plant species in the village of Detuwulu in Ende Regency used for traditional healing (Wae, Gago, and Ngapa 2022;Deda 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Studies on traditional healing practices within the Lio community have encompassed the documentation of Nijo healing ) and the compilation of a lexicon related to Lio healing practices (Genua 2018). Other folk medicine studies within the Lio community have focused on documenting Sua Soza, a healing mantra in the Ende language (Bala and Hua 2020), and the documentation of the Tu Gelu healing ritual, which involves the treatment of mystical ailments through the mediation of a traditional healer, involving the exchange of items representing livestock (Wula and Mboka 2021). Additionally, ethnobotanical studies recording the plant species utilized by the Lio people for traditional healing have shown that there are 47 plant species in the village of Waturaka and 52 plant species in the village of Detuwulu in Ende Regency used for traditional healing (Wae, Gago, and Ngapa 2022;Deda 2019).…”
Section: Introductionmentioning
confidence: 99%